(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
This paper examines using student engagement to increase academic success and performance in urban elementary schools. Urban students often fall behind in the achievement gap for a variety of reasons. The goal of this paper is to explain how increasing student engagement in inner-city schools can help to increase academic success. It outlines the different facets of student engagement—cognitive, behavioral, and emotional engagement, and explains the cyclical nature in which these three pieces come together to comprise student engagement. Taking cognitive, behavioral, and emotional engagement into consideration while planning and implementing lessons increases overall student engagement. Research-based strategies and suggestions are provided on how to incorporate each of the areas of student engagement to maximize student success.